Hemelipoglycoprotein from the ornate sheep tick, Dermacentor marginatus: structural and functional characterization - Dupejova, Jarmila; Sterba, Jan; Vancova, Marie; Grubhoffer, Libor (Parasites & vectors, 2011)
BACKGROUND: Tick carrier proteins are able to bind, transport, and store host-blood heme, and thus they function also as antioxidants. Nevertheless, the role of carrier proteins in ticks is not fully understood. Some of them are found also in tick males which do not feed on hosts to such an extent such as females (there are differences in male feeding in different tick species) and thus they are not dealing with such an excess of heme; some of the carrier proteins were found in salivary glands where the processing of blood and thus release of heme does not occur. Besides, the carrier proteins bind relatively low amounts of heme (in one case only two molecules of heme per protein) compared to their sizes (above 200 kDa). The main aim of this study is the biochemical characterization of a carrier protein from the ornate sheep tick Dermacentor marginatus, hemelipoglycoprotein, with emphasis on its size in native conditions, its glycosylation and identification of its modifying glycans, and examining its carbohydrate-binding specificity. RESULTS: Hemelipoglycoprotein from D. marginatus plasma was purified in native state by immunoprecipitation and denatured using electroelution from SDS-PAGE separated plasma. The protein (290 kDa) contains two subunits with molecular weights 100 and 95 kDa. It is glycosylated by high-mannose and complex N-glycans HexNAc(2)Hex(9), HexNAc(2)Hex(10), HexNAc(4)Hex(7), and HexNAc(4)Hex(8). The purified protein is able to agglutinate red blood cells and has galactose- and mannose-binding specificity. The protein is recognized by antibodies directed against plasma proteins with hemagglutination activity and against fibrinogen-related lectin Dorin M from the tick Ornithodoros moubata. It forms high-molecular weight complexes with putative fibrinogen-related proteins and other unknown proteins under native conditions in tick plasma. Feeding does not increase its amounts in male plasma. The hemelipoglycoprotein was detected also in hemocytes, salivary glands, and gut. In salivary glands, the protein was present in both glycosylated and nonglycosylated forms. CONCLUSION: A 290 kDa hemelipoglycoprotein from the tick Dermacentor marginatus, was characterized. The protein has two subunits with 95 and 100 kDa, and bears high-mannose and complex N-linked glycans. In hemolymph, it is present in complexes with putative fibrinogen-related proteins. This, together with its carbohydrate-binding activity, suggests its possible involvement in tick innate immunity. In fed female salivary glands, it was found also in a form corresponding to the deglycosylated protein.
Keywords: glykoproteiny; Animals; Electrophoresis, Polyacrylamide Gel; transportní proteiny; Hemagglutinins; Female; Immunoprecipitation; Glycosylation; ženské pohlaví; lipoproteiny; podjednotky proteinů; vazba proteinů; ovce; imunoprecipitace; hemoproteiny; zkřížené reakce; Antibodies; Glycoproteins; Dermacentor; Cross Reactions; Hemeproteins; Carrier Proteins; molekulová hmotnost; Male; Sheep; metabolismus sacharidů; glykosylace; hemaglutininy; Protein Subunits; Lipoproteins; zvířata; mužské pohlaví; Molecular Weight; elektroforéza v polyakrylamidovém gelu; Carbohydrate Metabolism; Protein Binding; Ornithodoros; protilátky